Auditory Neuropathy Spectrum Disorder in Late Preterm and Term Infants with Severe Jaundice - Saluja, Satish (2010)
OBJECTIVE: To evaluate if severe jaundice is associated with acute auditory neuropathy spectrum disorder in otherwise healthy late preterm and term neonates. METHODS: In a prospective observational study, all neonates who were admitted with severe jaundice at which exchange transfusion may be indicated as per American Academy of Pediatrics guidelines had comprehensive auditory evaluation performed before discharge to home. Neonates with infection, perinatal asphyxia, chromosomal disorders, craniofacial malformations, or family history of childhood hearing loss were excluded. Comprehensive auditory evaluations (tympanometry, oto-acoustic emission tests, and auditory brainstem evoked responses) were performed by an audiologist unaware of the severity of jaundice. Total serum bilirubin and serum albumin were measured at the institutional chemistry laboratory using the Diazo and Bromocresol purple method, respectively. RESULTS: A total of 13 neonates with total serum bilirubin concentration at which exchange transfusion is indicated as per American Academy of Pediatrics were admitted to the Neonatal Intensive Care Unit over 3 month period. Six out of 13 neonates (46%) had audiological findings of acute auditory neuropathy spectrum disorder. There was no significant difference in gestational age, birth weight, hemolysis, serum albumin concentration, peak total serum bilirubin concentrations, and peak bilirubin:albumin molar ratio between six neonates who developed acute auditory neuropathy and seven neonates who had normal audiological findings. Only two out of six infants with auditory neuropathy spectrum disorder had clinical signs and symptoms of acute bilirubin encephalopathy. CONCLUSIONS: Our findings strongly suggest that auditory neuropathy spectrum disorder is a common manifestation of acute bilirubin-induced neurotoxicity in late preterm and term infants with severe jaundice. Our findings also suggest that comprehensive auditory evaluations should be routinely performed in neonates with severe jaundice irrespective of the presence of clinical findings of acute bilirubin encephalopathy.